ANALISIS KEMAMPUAN LIERASI MATEMATIKA SISWA DALAM MENYELESAIKAN SOAL-SOAL MATEMATIKA JENIS PISA KELAS IX SMP NEGERI 1 SAGULING - Rohendi Rohendi; Wahyu Setiawan; Asep Ikin Sugandi (IKIP Siliwangi, 2023)
This study aims to analyze the mathematical literacy abilities of class IXA students at SMPN 1 Saguling through PISA type questions on Statistics material. The research was conducted at SMP N 1 Saguling class IXA with a sample of 29 research subjects. This study used descriptive qualitative method. The tool used in this research process is a three-item descriptive test. The research process was carried out by analyzing students' answers/responses to link statistical material with other data and contextual questions which were divided into three levels of competency classification: low, medium and high. The data analysis technique in this study is by condensing data, presenting data, and drawing or verifying conclusions. The results showed that the math literacy skills of the students of SMP Negeri 1 Saguling were moderate based on the test scores/responses collected.